A Study of Perceived Audit Quality and Size of Big 4 Audit Office - Jia , Hongmei; Hsiao, Daniel (Journal of Accounting and Finance, 2021)
This study examines whether investors perceive audit quality of Big 4 accounting firms uniformly across the firms’ office size. Specifically, we aim to explore whether large offices of Big 4 accounting firms associate with high level investors perceived audit quality. The empirical results from our regression analyses suggest that investors do place higher value for the audit work conducted by large size audit offices within Big-4 accounting firms. However, our further analyses indicate that the results cannot be generalized to those in non-Big-4 auditing firms.